Case report: Targeted treatment strategies for Erdheim-Chester disease - Gulyás, Anita; Pinczés, László Imre; Mátyus, János; Végh, Edit; Bedekovics, Judit; Tóth, Judit; Barna, Sándor; Hunya, Zsolt; Szabó, Imre Lőrinc; Gazdag, Annamária; Illés, Árpád; Magyari, Ferenc (Frontiers in Oncology, 2024)
Introduction Erdheim-Chester disease (ECD) is a rare disease that belongs to the group of Dendritic and histiocytic neoplasms. Only 2000 cases have been reported worldwide. It can present with a wide range of symptoms, making a differential diagnosis especially difficult. The primary and most important diagnostic tool is a biopsy of the affected organ/tissue. Nowadays the analysis of different mutations affecting the BRAF and MAPK pathways makes it possible to use targeted treatments, such as vemurafenib, dabrafenib, or cobimetinib. Objective Our aim is to present the results of three male patients treated in our hematology department. Results Our BRAF mutation-positive patient presented with retroperitoneal tissue proliferation and diabetes insipidus. The initial therapy of choice was dabrafenib. After 3 months of treatment, 18F-fluoro-deoxyglucose positron emission tomography (FDG-PET)/computed tomography (CT) scans showed regression, and after 2 years of treatment, no disease activity was detected. In our second patient, a recurrent febrile state (not explained by other reasons) and diabetes insipidus suggested the diagnosis. A femoral bone biopsy confirmed BRAF-negative ECD. The first-line therapy was interferon-alpha. After 3 months of treatment, no response was observed on 18FDG-PET/CT, and treatment with cobimetinib was started. The control 18FDG-PET/CT imaging was negative. Our third patient was evaluated for dyspnea, and a CT scan showed fibrosis with hilar lymphadenomegaly. A lung biopsy confirmed BRAF-negative ECD. We started treatment with interferon-alpha, but unfortunately, no improvement was observed. Second-line treatment with cobimetinib resulted in a partial metabolic response (PMR) according to control 18FDG-PET/CT. Conclusions Our results demonstrate that an appropriately chosen treatment can lead to a good therapeutic response, but dose reduction may be necessary due to side effects. With advanced targeted therapeutic treatment options, survival and quality of life are significantly improved.